PARENTS’ ROLE TOWARDS IMPROVING THE PERFORMANCE OF THEIR CHILDREN IN SCHOOL WORK: A CASE STUDY OF BINDURA PRIMARY SCHOOLS - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
The purpose of this present study was to investigate the role played by parents in improving theperformance of their children in school work in Bindura primary schools in Zimbabwe using thequantitative research methodology. The population consisted of all heads, SDC/SDA membersand teachers in the thirty schools in Bindura. Random sampling was used to arrive at a sampleof ninety six (96) respondents made up of six (6) heads of schools, seventy two (72) teachers andeighteen (18) members of School Development Committees or Associations (SDCs/SDAs). Thequestionnaire and interview were used for data collection. The study revealed that there aremany barriers to effective parental involvement in school activities such as lack of education byparents. The study recommends that heads of schools should always involve parents beforemaking decisions that require the inputs from the parents. There should also be staffdevelopment workshops for teachers and parents where parental involvement in the education oftheir children would be the main topic.